Implementation of the Trader Role Play Method to Improve the Social and Emotional Abilities of Early Childhood - Arif Nursihah; Heri Hidayat; Devy Oktaviany; Indah Sari Dewi. Z (Al Hikmah Indonesian Journal of Early Childhood Islamic Education, 2026)
Early childhood education contributes significantly to building the foundation of children's abilities, including social-emotional skills, which are the foundation that will foster a sense of security, the ability to socialize, communicate, and share with friends. However, observations show that most children aged 5-6 years still fight over toys, hit friends, get angry easily, and like to give orders. The purpose of this study is to improve social-emotional skills through the application of the trader role-play method. This study uses the classroom action research (CAR) model from Kemmis & Mc Taggart which was implemented in two cycles on 21 children in group B Raudhatul Athfal. Data collection was carried out through observation, performance assessment, interviews and documentation, then analyzed qualitatively with triangulation of techniques and sources. The results of the study showed an increase in social-emotional skills. In the first cycle, the majority of children were in the "sufficient" category, while in the second cycle there was a significant increase with many children reaching the "good" category. The application of trader role-play with various media, teacher reflection, and active child involvement has proven successful in creating more interactive and meaningful learning. This study concludes that the implementation of the trader role-play method is an effective strategy for stimulating early childhood social-emotional skills while strengthening self-confidence, adapting to their environment, and fostering social interactions. The practical contribution of this study is the implementation of the trader role-play method, which can be adapted by early childhood education teachers in their daily learning.